Simulacra in Webtoon Virgo and The Sparkling by Anisha Nisfihani - Eva, Sandika; Merawati, Fitri (Jurnal Sastra Indonesia, 2024)
This study aims to identify forms of simulacra, including signs, images, and codes, in the Webtoon Virgo and The Sparkling by Anisha Nisfihani. The research applies Jean Baudrillard's simulacra theory, which explains that representations and technological simulations have replaced contemporary reality. This study employs a descriptive qualitative method with a narrative analysis approach, utilizing data in the form of text and images from the Webtoon. The analysis reveals 71 forms of simulacra, consisting of 29 signs, such as guitars and costumes, 28 codes, such as "rental" and "synesthesia," and 14 images, such as the cool blue color or the smell of burning. Where each element conveys profound meanings that vary according to individual interpretation. The research demonstrates that Webtoons, as a form of cyber literature, are not merely entertaining but also encompass diverse meanings that illustrate how digital culture and media technology shape the understanding of reality. This study is expected to contribute to broadening insights into the application of simulacra theory in popular literature, particularly in understanding the role of Webtoons as an innovative platform in contemporary literature.